Cutaneous Chromatophoromas in Four Species of Australian Elapid Snake. (February 2021) - Taggart, Patrick L.; Woolford, Lucy; Dunstan, Nathan; Allen, Luke; Buote, Melanie; Lindsay, Scott A.
Summary: This report documents the clinicopathological features of cutaneous chromatophoromas in four wild-caught, captive Australian elapid snakes: a strap-snouted brown snake ( Pseudonaja aspidoryncha), a tiger snake ( Notechis scutatus ), an Eastern brown snake ( Pseudonaja textilis ) and a Mengden's brown snake ( Pseudonaja mengdeni ). All tumours were subclassified as melanophoromas, with three assessed as malignant on the basis of invasive growth or presence of intracoelomic metastases. The chromatophoromas were single or multiple, black or orange pigmented, cutaneous, sometimes ulcerated, plaques or nodules. Microscopically, the neoplastic cells were often spindle shaped with low or variable pigmentation. Neoplastic cells in one tumour were notable for their pleomorphic round cell morphology and high mitotic rate. One snake with late-stage metastasis survived for over 5 years. There are few reports of chromatophoromas in elapid snakes and, to our knowledge, this is the first report of these tumours in Australian elapid snakes.